Predictors of recovery from COVID-19: a retrospective study in one of the aspirational district of India - Katoch, Gurmeet; Sharma, Ekta; Guleri, Rajesh (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus disease 2019 (COVID-19) is the third corona virus that has emerged among the human population in last two decades. The main aim of this study was to describe the epidemiology and recovery predictors of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) patients admitted at COVID health facilities. Methods: A retrospective observational study was conducted from April 2020 to September 2020. The categorical and continuous variables were expressed as frequency, percentages and as mean and standard deviation respectively. Pearson chi square test and multivariable logistic regression were applied to ascertain the associations. Mean recovery time was compared by Kaplan-Meier analysis. Results: The mean age of participants was 36.8±17.54 years with a male preponderance. The age group of 20-39 years was the most affected group (43%). Age and pre-existing co morbidities were found to be significant factors affecting the recovery duration of patients. Mean recovery time with respect to age groups and gender was 15 and 18 days respectively. Mortality rate of 2% was recorded. Conclusions: In conclusion, COVID-19 affects a wide-range of population. Although age was not found to be a significant factor for acquiring the disease, however younger age group was significantly associated with early recovery. Considering our findings, we suggest additional measures to protect the vulnerable population.